Factors Affecting the Academic Performance of Bs Entrepreneurship Students: An Exploratory Analysis - Bongalonta, Michael B.; Despuig, Led L.; Bongalonta, Michelle M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explores the factors influencing the academic performance of third-year Bachelor of Science (BS) Entrepreneurship students at Sorsogon State University, Bulan Campus. The primary objective is to identify the socio-demographic characteristics, academic performance, and external factors that contribute to the students' academic success. This research employed a total enumeration method, collecting data from 70 students. Descriptive statistical tools, including frequency counts, means, percentages, and standard deviations, were utilized to analyze trends and patterns in the data. The findings reveal that the majority of the respondents are male, within the traditional college age range, and come from low-income families. The students demonstrated a generally high level of academic achievement, with an overall General Weighted Average (GWA) of 90.72. Personal factors, including motivation, study habits, and time management, emerged as the most significant determinants of academic success, followed by socioeconomic status and teaching strategies. The study also highlighted the importance of effective teaching methods and a supportive learning environment in enhancing student performance. Despite the academic achievements, financial constraints were identified as a significant barrier for many students, impacting their access to resources and overall academic experience.